2017
DOI: 10.1177/1687814016686265
|View full text |Cite
|
Sign up to set email alerts
|

Development of an automatic visual grading system for grafting seedlings

Abstract: In this study, a visual grading system of vegetable grafting machine was developed. The study described key technology of visual grading system of vegetable grafting machine. First, the contrasting experiment was conducted between acquired images under blue background light and natural light conditions, with the blue background light chosen as lighting source. The Visual C++ platform with open-source computer vision library (Open CV) was used for the image processing. Subsequently, maximum frequency of total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…With the data augmentation, such as the flip, brightness and saturation change, we enlarged the training data and created samples in different status, and this classification method we constructed still had a high accuracy. It showed strong robustness in classification ability against the traditional image processing method [1][2][3][4][5][6]. Because the different brightness or saturation of image samples may affect the segmentation result or any other algorithm effect in traditional image processing, so as to reduce the accuracy.…”
Section: Plug Seedlings Classification Test Rusultmentioning
confidence: 99%
See 1 more Smart Citation
“…With the data augmentation, such as the flip, brightness and saturation change, we enlarged the training data and created samples in different status, and this classification method we constructed still had a high accuracy. It showed strong robustness in classification ability against the traditional image processing method [1][2][3][4][5][6]. Because the different brightness or saturation of image samples may affect the segmentation result or any other algorithm effect in traditional image processing, so as to reduce the accuracy.…”
Section: Plug Seedlings Classification Test Rusultmentioning
confidence: 99%
“…Qingchun et al used structured light and industrial camera methods to identify seedlings by detecting leaf area and stem height, and the recognition accuracy was over 90% [4]. Tian et al extracted the measurements of scion and rootstock stem diameters to grade scion and rootstock seedlings [5]. Wang et al compared the pixel value of seedling with threshold value to determine whether the cell was short of seedlings according to the binary images of the plug tray.…”
Section: Introductionmentioning
confidence: 99%
“…Its productivity was determined by the number of modules applied, and this robot is suitable for small-to medium-sized farms [21] . Research on the key technologies of grafting robots were also reported, such as outward-feature properties measurement of seedlings [31] , grafting quality or healing state detection [32,33] , and seedlings classification [34,35] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of machine vision has been employed too in grading grafting seedlings in a study carried out by Tian et al (2017). A success rate of 98% was achieved exhibiting that their developed vision system was helpful in improving the grading accuracy and efficiency.…”
Section: Introductionmentioning
confidence: 99%